Allogeneic transplant following brentuximab vedotin in patients with relapsed or refractory Hodgkin lymphoma and systemic anaplastic large cell lymphoma. Issue 3 (March 2015) - Illidge, Tim; Bouabdallah, Reda; Chen, Robert; Gopal, Ajay K.; Moskowitz, Craig H.; Ramchandren, Radhakrishnan; Shustov, Andrei R.; Tilly, Herve; Trippett, Tanya M.; Gibb, Adam; Grove, Laurie E.; Advani, Ranjana
Abstract: Brentuximab vedotin is an antibody drug conjugate that induces durable objective responses in patients with relapsed or refractory Hodgkin lymphoma and systemic anaplastic large cell lymphoma. Fifteen of 160 patients who participated in two pivotal phase 2 studies received a consolidative allogeneic stem cell transplant (allo-SCT) following brentuximab vedotin treatment. This case series describes their experience. The studies were approved by Institutional Review Boards prior to patient enrollment. Patients received 1.8 mg/kg brentuximab vedotin every 3 weeks for up to 16 cycles. The estimated 2-year progression-free survival (PFS) rate was 66%, and the median PFS has not yet been reached. Eleven of the 15 patients were alive and the estimated 2-year survival rate was 80%. The safety of brentuximab vedotin treatment in this series was consistent with the known safety profile in this setting. Brentuximab vedotin is a compelling option for reducing tumor burden to facilitate a consolidative allo-SCT.